Anterior abdominal wall abscess secondary to spontaneous rupture of liver abscess in a resource-limited, rural, surgical setting: A case report - Royson Dsouza; Mrudula Rao; Harshad Arvind Vanjare; Manbha Rymbai (Health for All Nations, 2021)
Liver abscess continues to be a major surgical burden in low-and mid-low-income countries like India. Spontaneous rupture into the anterior abdominal wall is an uncommon presentation of pyogenic liver abscess. A 53-year-old diabetic female presented with acute pain in the right, upper quadrant of the abdomen. On examination, she had an anterior abdominal wall abscess with tender hepatomegaly. On further evaluation with ultrasonography and plain computed tomography, a diagnosis of liver abscess in the right lobe with rupture into the anterior abdominal wall was made. She was treated successfully in a tribal secondary care hospital with an ultrasound-guided aspiration followed by surgical drainage under local anesthesia. This case report highlights that a considerable number of patients with liver abscess and its complications can be appropriately managed in resource-limited, rural, surgical centers.